2006
DOI: 10.1074/jbc.m606179200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Amino Acid Side Chains in Region 17–31 of Parathyroid Hormone (PTH) in Binding to the PTH Receptor

Abstract: Parathyroid hormone (PTH)2 plays a key role in calcium and phosphate homeostasis and has potent effects on the bone-remodeling process. PTH interacts with a Class 2 G protein-coupled receptor that is prominently expressed in bone osteoblasts and in cells located in the proximal and distal portions of the renal convoluted tubules. The PTH receptor (PTHR) is also expressed in the primordia of developing long bones, heart, mammary glands, and other tissues, where it mediates the morphogenic actions of PTH-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…In particular, replacement of the four core residues (R20, W23, L24, and L28) with alanine markedly reduced PTH binding, with mutations in the three hydrophobic residues nearly abolishing PTH binding to the ECD. Our data are in good agreement with the recent study of alanine-scanning of PTH-(17-31) (29). These results thus further support the detailed molecular interactions observed in our crystal structure.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…In particular, replacement of the four core residues (R20, W23, L24, and L28) with alanine markedly reduced PTH binding, with mutations in the three hydrophobic residues nearly abolishing PTH binding to the ECD. Our data are in good agreement with the recent study of alanine-scanning of PTH-(17-31) (29). These results thus further support the detailed molecular interactions observed in our crystal structure.…”
Section: Resultssupporting
confidence: 82%
“…Crystals of the purified MBP-PTH1R-ECD bound to a synthetic PTH fragment (residues [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] were grown in hanging drops containing a reservoir solution of 100 mM sodium cacodylate (pH 6.5) and 30% (vol/vol) polypropylene glycol P400 (PPG P400). Diffraction data were collected at 21-ID-D (LS-CAT) of the Advanced Photon Source at Argonne National Laboratory (Argonne, IL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the results of an Ala scanning analysis described by Dean et al [31] and of the recently published crystal structure of a PTH (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) peptide in complex with the PTH1R ectodomain [12]. Here, we extend these investigations by testing the whole PTH ligand for interactions.…”
Section: Accepted M Manuscriptsupporting
confidence: 91%
“…6B). Moreover, structureactivity relationship studies focused on this position have shown that even structurally related amino acid substitutions have significant and deleterious impacts on receptor binding affinity (Barbier et al, 2001;Dean et al, 2006a). Thus the contacts identified in the crystal structures between the Arg20 side chain and the receptor must play a key and critical role in docking the ligand to the ECD and/or maintaining the stability of the ligand/ receptor complex once it is formed.…”
Section: Parathyroid Hormone Receptors and Their Ligandsmentioning
confidence: 99%